Introduction to special section 1: Anthropology and character. (23rd February 2018) - Reed, Adam; Bialecki, Jon
Abstract : This introductory essay seeks to reintroduce character to anthropological inquiry. Although it has long been out of favour due to its historical associations with accounts that attempt to describe national or ethnic character, we argue that a return of the under‐theorised concept may be in order. The essay invites socio‐cultural anthropologists to describe the diverse contexts in which character is recognised or enacted, out‐there‐in‐the‐world, and to become far more reflective about the ways in which characterization is deployed in our ethnographic writing. At the same time, it asks how the concept might be fruitfully operationalized at a meta‐language level to reorient current fields of anthropological study, without necessarily resorting to any collective or individual essentialisms. To illustrate the utility of re‐interrogating the concept, the question is addressed to two specific fields in which one might expect a concept such as character to already feature strongly: the anthropology of ethics and the anthropology of Christianity. What does an ethnographic attention to the ways in which character gets attributed reveal? How differently might these and other fields look if anthropologists embraced the concept of character or rejected it more knowingly? Finally, the essay asks what kinds of recombination of insights an anthropology and character approach might enable.